1980
DOI: 10.1111/j.1365-2125.1980.tb04796.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the passage of drugs from blood into saliva.

Abstract: 1. Following single oral dosing of ampicillin, cephalexin, tetracycline, erythromycin estolate, clindamycin and rifampicin to six normal volunteers, antibacterial activity was measured at 1, 3 and 6 h in serum, gingival fluid and minor gland saliva from all subjects and in parotid and submandiabular saliva from three. 2. pH values of all gingival fluid and saliva specimens were noted. 3. Partition coefficients between n‐octanol and water were measured for erythromycin, clindamycin and rifampicin. Published dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 13 publications
0
6
0
4
Order By: Relevance
“…Kleinberg and Hall (1969) reported pH values from 7.78 to 8.73 in gingival crevices and correlated these values to the pH of supragingival plaque. Stephen et al (1980) found a pH ranging from 7.5 to 8.0 for gingival fluid. They estimated the pH with universal indicator paper in situ.…”
Section: Discussionmentioning
confidence: 97%
“…Kleinberg and Hall (1969) reported pH values from 7.78 to 8.73 in gingival crevices and correlated these values to the pH of supragingival plaque. Stephen et al (1980) found a pH ranging from 7.5 to 8.0 for gingival fluid. They estimated the pH with universal indicator paper in situ.…”
Section: Discussionmentioning
confidence: 97%
“…In another study 0.71 mg/L ER was measured in saliva 2 h after administration of 500 mg ER propionate [10]. In contrast Stephen et al could not detect ER in saliva after administration of 2×250 mg ER estolate [11].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics accumulated in salivary gland tissue are excreted in saliva, which is easily collected. The levels of these substances in saliva reflect concentrations in the gland tissue [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…Typical is an intact border of enamel along the oral and facial gingival margin. The reason for the preserved enamel band could be due to some plaque remnants, which could act as a diffusion barrier for acids [Schweizer-Hirt et al, 1978], or due to an acid neutralizing effect of the sulcular fluid, which has a pH between 7.5 and 8.0 [Stephen et al, 1980]. Further acid attacks can lead to pseudo-chamfers at the margin of the eroded surface.…”
Section: Diagnosis and Distributionmentioning
confidence: 99%